Cas12a Cis-cleavage mediated lateral flow assay enables multiplex and ultra-specific nucleic acid detection - Mei Lin; Zhiqiang Qiu; Mengen Hao; Weiwei Qi; Ting Zhang; Yuting Shen; Hongrui Xiao; Chaoyue Liang; Longxu Xie; Yongzhong Jiang; Meng Cheng; Tian Tian; et al. (Nature Communications)
Abstract CRISPR technology holds significant promise for advancing nucleic acid assays. However, current CRISPR diagnostic techniques, reliant on indiscriminate trans-cleavage mechanisms, face challenges in developing multiplex detection formats. Moreover, chaotic trans-cleavage activity often results from mismatched targets, leading to specificity issues. To address these limitations, here we exploit a double-key recognition mechanism based on CRISPR-Cas12a cis-cleavage and invasive hybridization identification of released sticky-end DNA products. By integrating multiplexed nucleic acid amplification, the double-key Cas12a detection mechanism, and a lateral flow detection platform, we develop a method termed Cas12a cis-cleavage mediated lateral flow assay (cc-LFA). We demonstrate that the cc-LFA exhibited superior specificity compared to three mainstream trans-cleavage-based CRISPR diagnostic techniques, achieving single-base resolution detection free from high-concentration wild-type DNA background interference. cc-LFA is also applied for highly specific detection of multiple respiratory pathogen samples and precise multiplexed detection of nine high-risk human papillomavirus (HPV) subtypes, achieving over 90% sensitivity and 100% specificity, respectively. Additionally, we present a portable device to automate nucleic acid amplification and strip detection procedures, showcasing the potential of cc-LFA for future applications in decentralized laboratory scenarios.